“I don’t want to be here”: Perceptions of persistence among lgbtq+ students of color at predominantly white institutions of higher education - Jorgenson, Christopher J. (My University, 2020)
LGBTQ+ college students of color–living at the nexus of race, sexuality, and gender–are at risk of higher rates of attrition, exacerbated by institutions whose student enrollment is predominantly White. This study used qualitative methods to explore and better understand the experiences of LGBTQ+ college students of color at predominantly White institutions, in order to determine barriers to persistence and effective strategies for institutional education, advocacy, and support. Findings suggest students whose identities encompass intersectional marginality experience disproportionate discrimination, bigotry, and exclusion–individually and institutionally. Predominant Whiteness is both intrusive and reflective of campus environments designed for and maintained by White supremacy and cisheteropatriarchy. LGBTQ+ college students of color, absent from the majority of strategic enrollment processes in higher education, often regard their campuses as indifferent, apathetic, and wholly unwilling to affect substantive change. The study concludes with several recommendations. Predominantly White institutions of higher education must engage more deeply with culturally responsive educational training and engagement that focuses on power and its inequitable distribution and exercise. Faculty and staff representation across the institution should reflect the identities of the students they serve; PWIs must actively recruit and work to retain faculty and staff who are themselves LGBTQ+ people of color.
Keywords: Education; College Students; Discrimination in higher education